2004
DOI: 10.1002/ajpa.10270
|View full text |Cite
|
Sign up to set email alerts
|

Bony ponticles of the atlas (C1) over the groove for the vertebral artery in humans and primates: Polymorphism and evolutionary trends

Abstract: The aim of this study was to ascertain the distribution in primates of the three possible bony ponticles over the groove for the vertebral artery (ventral, lateral, and dorsal ponticles), in order to attempt to understand the variants observed in humans and to ascertain possible evolutionary trends in primates. The material consisted of 393 atlases of extant nonhuman primates representative of 41 genera, and of 500 human atlases (dried bones of adults). For each atlas, we studied the existence and morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“…This osseous bridge has been called by various names in the literature: atlantic ponticulus, posterior ponticulus, bony ponticles over the groove for the VA, and posterior bridging of the atlas. 4,6,10,13,15,20 Previous studies of dry bones or cadavers have found osseous bridges in 5.0-34.66%. 10,13,15,17,20,23 On radiographic studies, the bridge was found in 11-15.6%.…”
Section: Anatomical Variations and Anomaliesmentioning
confidence: 97%
See 1 more Smart Citation
“…This osseous bridge has been called by various names in the literature: atlantic ponticulus, posterior ponticulus, bony ponticles over the groove for the VA, and posterior bridging of the atlas. 4,6,10,13,15,20 Previous studies of dry bones or cadavers have found osseous bridges in 5.0-34.66%. 10,13,15,17,20,23 On radiographic studies, the bridge was found in 11-15.6%.…”
Section: Anatomical Variations and Anomaliesmentioning
confidence: 97%
“…4,6,10,13,15,20 Previous studies of dry bones or cadavers have found osseous bridges in 5.0-34.66%. 10,13,15,17,20,23 On radiographic studies, the bridge was found in 11-15.6%. 4,11,20,24 The incidence of osseous bridges in our study was lower than those in past reports, and it is difficult to explain the cause of this wide disparity.…”
Section: Anatomical Variations and Anomaliesmentioning
confidence: 97%
“…The atlas bridges are a shared structure between human and non-human primates. The posterior bridge is found dorsal to the lateral mass on the posterior arch of the atlas (Le Minor & Trost, 2004) and when complete, forms the retroarticular canal (Mitchell, 1998a(Mitchell, , 1998b) also called a Kimmerle's variant (Kimmerle, 1930) or arcuate foramen (Von Torklus & Gele, 1972). Lateral bridges, are less common than the posterior and may also exist as complete foramina (Mitchell, 1998a(Mitchell, , 1998b, called the supratransverse foramina (Chevrel et al, 1965 cited by Le Minor & Trost).…”
Section: Introductionmentioning
confidence: 99%
“…As for atlas bridging in extant nonhuman primates, there are only a few studies (Loth-Niemerycz, 1916;Sato and Noriyasu, 1978;Yamamoto and Kunimatsu, 2002a, b;Le Minor and Trost, 2004), most of which were based on analysis at the genus or family levels. These studies showed that prevalence of atlas bridges in humans is much lower than in the other primate taxa.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that prevalence of atlas bridges in humans is much lower than in the other primate taxa. Le Minor and Trost (2004) studied atlas bridges in 41 genera of extant nonhuman primates and discussed possible evolutionary trends. In their study, however, the material lacked data such as age and sex, and, except for the hominoids, the data were analyzed at the generic level.…”
Section: Introductionmentioning
confidence: 99%